Effect of fetal distress on viability and yield of umbilical cord blood stem cells–a prospective comparative study - Bharathi Muthu; Prabhu Manivannan; Murali Subbaiah; Shreya Vanju; Abhishekh Basavarajegowda (Hematology, Transfusion and Cell Therapy)
Introduction: Different factors affect the quality and viability of cord blood stem cells, and therefore the efficacy of umbilical cord stem cell transplantation. Fetal distress is one factor affecting the quantity of CD34+ cells in cord blood. This study was designed to compare the viability and yield of the umbilical cord blood stem cells of women who have undergone emergency lower segment caesarean section for fetal distress or for other causes. Materials and methods: This cross-sectional analytical study was performed at a tertiary care hospital facility with a total sample size of 68: 34 participants had undergone emergency C-section for fetal distress, and 34 had undergone emergency C-section for other causes. Umbilical cord blood was collected ex-utero in a 350 mL bag with citrate-phosphate-dextrose solution with adenine. Three milliliter of blood were transferred to an ethylenediaminetetraacetic acid (EDTA) tube for cell counts and flow cytometry testing for CD34+. The chi-square test was used to compare the total mononuclear cell, CD34+, and viability between the groups. Results: The CD34+ count [mean 4.9 versus 1.1 (× 106 cells/unit)] and total nucleated cell count [mean 14.2 versus 7.5 (× 108/unit)] were significantly higher in cord blood units collected from women who delivered by C-section for fetal distress (p-value <0.05). However, the volume of umbilical cord stem cells and viability of stem cells did not vary significantly based on the presence or absence of fetal distress (p-value >0.05). Conclusion: The current study shows that umbilical cord blood collected during fetal distress has a significantly higher content of stem cells and total nucleated cells than the non-fetal distress group